Highly Hydrophobic Isoreticular Porous Metal–Organic Frameworks for the Capture of Harmful Volatile Organic Compounds1. Issue 32 (26th June 2013) - Padial, Natalia M.; Quartapelle Procopio, Elsa; Montoro, Carmen; López, Elena; Oltra, J. Enrique; Colombo, Valentina; Maspero, Angelo; Masciocchi, Norberto; Galli, Simona; Senkovska, Irena; Kaskel, Stefan; Barea, Elisa; et al.
<x xml:space="preserve">Abstract</x> Tunable hydrophobicity: Efficient air filters for the protection against chemical warfare agents might be achieved by surface functionalization of the pores in robust metal–organic frameworks (MOFs) with fluoroalkyl residues and the precise control of their pore size (see picture). These MOFs capture harmful volatile organic compounds even under extremely moist conditions (80 % relative humidity).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>